Isolation of enterobacteriaceae bacteria species from feces of Sumatran Orangutans (Pongo abelii) - . Darmawi; Erdiansyah Rahmi; Maryulia Dewi; Joharsyah Hutabarat; Mahdi Abrar; . Fakhrurrazi (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
The porpouse of this research aimed to isolate enterobacteriaceae bacteria from feces of Pongo abelii. The samples of feces were collected from 15 captive orangutans in Orangutan Sumatera Batu Mbelin Sibolangit Qurantine, North Sumatra. Of each sample was cultured in nutrient broth media using sterilecotton swabs or Pasteur pipettes, and incubated at 37°C temperature for 24 hours. Culture was spared on Methylene Blue Agar (Oxoid), examined by Gram staining, and tested by biochemically. The result showed that significantly more common appear Escherichia sp. (93,33%) and fewer Edwardsiella sp. (66,67%) wereisolated from feces samples of P. abelii. Others enterobacteriaceae found in feces of P. Abelii were Shigella sp. (46,67%), Klebsiella sp. (33,33%), Citrobacter sp., and Salmonella sp. (13,33%), respectively